2021
DOI: 10.3390/vaccines9040362
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Modified Live Virus Vaccine: A “Leaky” Vaccine with Debatable Efficacy and Safety

Abstract: Porcine reproductive and respiratory syndrome (PRRS) caused by the PRRS virus (PRRSV) is one of the most economically important diseases, that has significantly impacted the global pork industry for over three decades, since it was first recognized in the United States in the late 1980s. Attributed to the PRRSV extensive genetic and antigenic variation and rapid mutability and evolution, nearly worldwide epidemics have been sustained by a set of emerging and re-emerging virus strains. Since the first modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 161 publications
0
59
0
Order By: Relevance
“…Whilst PRRS MLV vaccines can provide a significant clinical benefit, the protection against virus shedding is limited which may drive the evolution of PRRSV ( 55 , 56 ). This has been attributed to these vaccines being weakly immunogenic, especially for cellular responses ( 8 ). In line with previous reports, we confirmed that PRRS MLV vaccinated pigs recorded lower lung lesions, viraemia and viral load in lungs after a single infection with PRRSV-2, which was associated with a robust, although non-neutralizing, antibody response and a weak peripheral PRRSV-specific T cell response ( 11 , 14 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst PRRS MLV vaccines can provide a significant clinical benefit, the protection against virus shedding is limited which may drive the evolution of PRRSV ( 55 , 56 ). This has been attributed to these vaccines being weakly immunogenic, especially for cellular responses ( 8 ). In line with previous reports, we confirmed that PRRS MLV vaccinated pigs recorded lower lung lesions, viraemia and viral load in lungs after a single infection with PRRSV-2, which was associated with a robust, although non-neutralizing, antibody response and a weak peripheral PRRSV-specific T cell response ( 11 , 14 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both species have since spread globally, but PRRSV-1 remains predominant in Europe, while PRRSV-2 predominates in the Americas and Asia. The rapid evolution of PRRSV due to a high mutation rate when replicating its genome, and recombination between strains have resulted in substantial genetic diversity, which poses challenges for the control of PRRS by vaccination ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst PRRS MLV vaccines can provide a significant clinical benefit, the protection against virus shedding is limited which may drive the evolution of PRRSV (54,55). This has been attributed to these vaccines being weakly immunogenic, especially for cellular responses (8). In line with previous reports, we confirmed that PRRS MLV vaccinated pigs recorded lower lung lesions, viraemia and viral load in lungs after a single infection with PRRSV-2, which was associated with a robust, although non-neutralizing, antibody response and a weak peripheral PRRSV-specific T cell response (11,14,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the application of live vaccines might result in PRRSV variants that cause clinical severity and elevated viremia in the naïve inoculated pigs, suggesting a reversal of virulence level ( Jiang et al, 2015 ; Liu et al, 2018 ). Although mechanisms are unknown ( Zhou et al, 2021 ), tolerance after vaccination could facilitate genetic diversification of the circulating viruses, enabling them to evolve newer immune evasion strategies and revive virulence. Indeed, a recent study on chicken vaccinated against infectious bronchitis virus (IBV) has detected selection pressure, resulting in the diversification of viral coat proteins ( Franzo et al, 2019 ).…”
Section: Role Of Tolerance In Spillover and New Infectionsmentioning
confidence: 99%